Motifs of Disguise/ Imitation in European Literary Tradition (From Antiquity to the Eighteenth Century): Comic Effect vs. Tragic Pathos (University of Bucharest Review. Literary and Cultural Studies Series, 2025)
The article defines and examines the connection between the disguise/imitation motifs and the categories of comic and tragic within European literary tradition (from Antiquity to the Eighteenth century). The authors of this research explain the factors that make these motifs popular means of creating comic effect or tragic pathos and highlight the trends in their functioning. Disguise/imitation motifs are shown to be mostly related to situations that violate the usual norms of conformity, hierarchical relations, behavioural canons, and for this precise reason, they have a powerful affective potential, i.e. become capable of evoking strong emotions. The disguise/imitation motifs are appropriate for comic effect due to their archaic genetic links with ritual-laughter culture and their conformity to the very nature of the comic, which is based on contradictions. Tragic pathos arises as a result of tragic consequences of one’s identity loss within disguise/imitation situations, it prompts awareness of the injustice of society and the “cruelty” of fate, which are the cause of the forced rejection of one’s self. The article indicates the prospects of researching disguise/imitation motifs in modern art, where they are often employed in adventurous narratives to increase the plot’s dynamism, heighten dramatic tension, and intensify intrigue.